2011
DOI: 10.1177/0164027511423538
|View full text |Cite
|
Sign up to set email alerts
|

Equitable Access to Health Care for the Elderly in South Korea

Abstract: The aim of this study was to examine whether the principle of "equal treatment in equal need" was met in health care utilization in Korea regardless of income among the elderly. Using data from the Korean National Health and Nutrition Examination Survey for 1998Survey for , 2001Survey for , and 2005, the authors measured the horizontal inequity of health care utilization and identified the factors contributing to inequality. There were income-related inequalities favoring the better-off for both outpatient a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…However, the older adults with lower income are limited by transportation costs, information costs, service costs, etc., and their perceived vulnerability has also increased. They are more willing to use healthcare services nearby, choose some less expensive healthcare services, and reduce using frequency [34]. Seriously, low-income families are more willing to give up the expense on healthcare services [35], thereby reducing the willingness to use healthcare services.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…However, the older adults with lower income are limited by transportation costs, information costs, service costs, etc., and their perceived vulnerability has also increased. They are more willing to use healthcare services nearby, choose some less expensive healthcare services, and reduce using frequency [34]. Seriously, low-income families are more willing to give up the expense on healthcare services [35], thereby reducing the willingness to use healthcare services.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…Findings of the reviewed articles showed that with the increase of age, the need to use health services increases [3,15,25,33,37,39,40,43,50,53,54,56,59], but in some studies, with increasing age and exceeding 85 years, the use of health services decreased [55,58,61]. Gender was associated with access to health services such that women were significantly more likely to seek health services [5,9,15,17,25,30,39,43,45,49,50,52,53,54,58,59,61,64]. Married people used more health services than divorced, single, and never married people [25,30,43,52,57,60].…”
Section: Resultsmentioning
confidence: 99%
“…Shorter duration or distance in access to health care centers increased the likelihood of using health services in the elderly [3,46]. Having chronic diseases [1, 5, 9, 12, 16, 17, 25, 40, 42, 43, 47, 49, 52-55, 57, 59], low mental health, depression [38,46,49,50,57,61], cognitive impairment [61], physical disability [25], low self-assessed health status [3,5,9,12,15,31,50,52,53,59], correct perception of the problem [46], need for health care services [15,58], comorbid diseases [55], feeling pain [25,46] and unhealthy lifestyle (smoking and alcohol consumption) [25] were associated with using more outpatient health services (Table 1).…”
Section: Number Of Related Studies Factorsmentioning
confidence: 99%
“…From high school economics relating to health care accessibility (Moscelli et al, 2018;Nishide et al, 2017), health care utilization (Kim et al, 2011;Vásquez et al, 2013), and health status (Shahidi et al, 2018;Wildman, 2003).…”
Section: Financial Educationmentioning
confidence: 99%
“…As socioeconomic inequality has widened in many social domains including health, employment, education and even social networks, researchers and policymakers have become increasingly interested in accurately representing indicators of inequality. For example, studies on healthcare utilization or health outcomes have found that overall progress in health‐related resources might not be advantageous for all members of a group (Kim et al, 2011; Mangalore et al, 2007; Sortso et al, 2017; Vahedi et al, 2018). This finding implies that compared to better‐off individuals, worse‐off individuals do not have easy access to healthcare or resources due to financial barriers.…”
Section: Literature Review and Conceptual Backgroundmentioning
confidence: 99%